EVALUATION OF THE EFFECTIVENESS OF PROPHYLACTIC NOREPINEPHRINE DOSES IN PREVENTING MATERNAL HYPOTENSION AND THEIR EFFECTS ON NEONATES DURING SPINAL ANESTHESIA FOR CESAREAN SECTION AT HAI PHONG OBSTETRICS AND GYNECOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the effectiveness of prophylactic prevention of hypotension during spinal anesthesia for cesarean section and its effects on neonates when intravenous norepinephrine is administered at different infusion doses.Materials and methods: The study included 90 parturients aged over 18 years, with singleton, full-term pregnancies, and no contraindications to spinal anesthesia for cesarean delivery. The participants were randomly assigned into three groups to receive prophylactic intravenous norepinephrine infusion after spinal anesthesia at doses of 0.025 µg/kg/min, 0.05 µg/kg/min, and 0.075 µg/kg/min, respectively. The primary outcome measures included the incidence of hypotension; hypertension; bradycardia; nausea and vomiting; Apgar scores at 1 and 5 minutes and umbilical arterial blood gas parameters.Results: The incidence of hypotension in the 0.05 µg/kg/min group (16.6%) and the 0.075 µg/kg/min group (13.3%) was significantly lower than that in the 0.025 µg/kg/min group (39.9%) (p < 0.05). The incidence of hypertension in the 0.075 µg/kg/min group was 3.3% (n = 1); however, this difference was not statistically significant compared with the other two groups. There were no significant differences among the three groups in terms of maternal bradycardia, nausea and vomiting, Apgar scores at 1 and 5 minutes, or umbilical arterial blood gas results (p > 0.05).Conclusion: Intravenous norepinephrine infusion at doses of 0.05 µg/kg/min and 0.075 µg/kg/min effectively reduced the incidence of hypotension after spinal anesthesia for cesarean section. The dose of 0.075 µg/kg/min may be associated with an increased risk of hypertension. There were no significant differences among the three groups regarding the incidence of bradycardia, nausea and vomiting, neonatal Apgar scores, or umbilical arterial blood gas parameters.
Keywords: Noradrenaline, hypotension, spinal anesthesia for cesarean section, prophylaxis.